Thermal conductivity of aqueous mixtures of 2-n-butoxyethanol at pressures up to 150 MPa - Mensah-Brown, H.; Wakeham, W.A. (Journal of Chemical and Engineering Data, 2010)
This paper contains the results of new measurements of the thermal conductivity of mixtures of water and 2-n-butoxyethanol in the liquid phase within the temperature range of (304 to 346) K at pressures up to 150 MPa. The measurements were carried out with a transient hot-wire instrument and have an accuracy of ± 0.3 %. The investigation is the first conducted at high pressures on partially miscible mixtures whose components are of greatly differing thermal conductivity. It therefore provides a severe test of the methods of representing the thermal conductivity of liquid mixtures that are based on the hard-sphere theory of transport in liquids. It is shown that all of the experimental data may be represented to within ± 6 % by a "predictive" procedure based on the hard sphere theory of liquids. However, a more detailed analysis of the results reveals small but systematic deviations from the universal behavior of the thermal conductivity as a function of molar volume that the predictive procedure and the hard-sphere theory have as their basis. © 2010 American Chemical Society.